2001
DOI: 10.1111/j.1750-3639.2001.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HSV‐1 LAT in Human Trigeminal, Geniculate, and Vestibular Ganglia and Its Implication for Cranial Nerve Syndromes

Abstract: Herpes simplex virus type 1 (HSV-1) enters sensory neurons and can remain latent there until reactivation. During latency restricted HSV-1 gene expression takes place in the form of latency-associated transcripts (LAT). LAT has been demonstrated to be important not only for latency but also for reactivation, which may cause cranial nerve disorders. Tissue sections of the trigeminal ganglia (TG), geniculate ganglia (GG), and the vestibular ganglia (VG) from seven subjects were examined for the presence of LAT u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 35 publications
1
70
0
4
Order By: Relevance
“…Several studies have suggested that a viral agent may be the underlying cause of VN, either by demonstrating the presence of herpes simplex virus DNA within vestibular nerve fibers and "Scarpa's" ganglion or by demonstrating histologic changes within the vestibular nerve suggestive of viral-induced atrophy and inflammation. [11][12][13][14][15] On the other hand, an uncertain proportion of acute peripheral vestibular disorders are likely due to a vascular lesion of the nerve, and patients with such lesions may be at increased risk for future vascular events. [16] One study has suggested that age difference (50 years) plays an important role in differentiating between these two possible pathologies, however we were not able to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that a viral agent may be the underlying cause of VN, either by demonstrating the presence of herpes simplex virus DNA within vestibular nerve fibers and "Scarpa's" ganglion or by demonstrating histologic changes within the vestibular nerve suggestive of viral-induced atrophy and inflammation. [11][12][13][14][15] On the other hand, an uncertain proportion of acute peripheral vestibular disorders are likely due to a vascular lesion of the nerve, and patients with such lesions may be at increased risk for future vascular events. [16] One study has suggested that age difference (50 years) plays an important role in differentiating between these two possible pathologies, however we were not able to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of vestibular neuritis remains controversial and whilst labyrinthine ischaemia has been proposed, for the majority of patients, the natural history of the condition hints at an inflammatory cause, possibly due to reactivation of neurotropic viruses [2,22]. One study probed the effects of corticosteroids with and without antivirals and concluded that methylprednisolone, but not valacyclovir, improves the recovery of vestibular function in these patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…The many terms -vestibular neuritis / neuronitis / neuropathy / neuronopathy, acute vestibulopathy, acute vestibular neurolabyrinthitis, acute labyrinthitis 1 -often used interchangeably to describe PVP, testify to the fact that there is still much to be discovered about the nature of the disease.A less disputed issue is the fact that PVP is often preceded by a viral infection of the upper respiratory tract [37] or the higher prevalence (compared to controls) of Herpes viruses in the eighth and other cranial nerves and their neurons [1,12,17,41] as well as in the saliva of patients with PVP [33]. One animal study also supports the etiopathogenetic role of Herpes viruses, but points to histopathological changes in both the vestibular nerve and labyrinth [13].…”
Section: Etiology and Pathogenesis Of Pvp: The Evidence So Farmentioning
confidence: 75%